Effect of Positional Distribution of Linoleic Acid on Oxidative Stability of Triacylglycerol Molecules Determined by 1H NMR. (15th January 2015) - Wang, Xiang‐Yu; Yang, Dan; Gan, Lu‐Jing; Zhang, Hua; Shin, Jung‐Ah; Lee, Yong‐Hwa; Jang, Young‐Seok; Lee, Ki‐Teak
Abstract: 1 H nuclear magnetic resonance ( 1 H NMR) was used to determine the effect of positional distribution of linoleic acid (L) on the oxidative stability of triacylglycerols. For this purpose, structured soybean oil (SSO), which had a similar total fatty acid composition but a different L positional distribution than soybean oil (SO), was produced by interesterification reaction. The SO and SSO were oxidized in the dark at 40 °C. Afterwards, 1 H NMR was used to monitor the oxidation process and quantify the main polyunsaturated fatty acid, Z, E ‐ and E, E ‐conjugated forms, hydroperoxides, and aldehydes at different oxidation periods in a single run. After 45 days of oxidation, SSO showed lower L content than SO (9.9 ± 1.1 and 16.8 ± 0.5 %, respectively). Additionally, secondary oxidation products in SSO were shown to be more abundant than in SO (82.3 ± 4.9 and 43.6 ± 0.9 mmol/L oil, respectively). This study indicated that SO, which contains a higher distribution of L at the sn ‐2 position, was more resistant to autoxidation than SSO.